Molecular Characterization of Fecal Extended-Spectrum β-Lactamase- and AmpC β-Lactamase-Producing Escherichia coli From Healthy Companion Animals and Cohabiting Humans in South Korea - Hong, Jun Sung; Song, Wonkeun; Park, Hee-Myung; Oh, Jae-Young; Chae, Jong-Chan; Jeong, Seri; Jeong, Seok Hoon (Frontiers in Microbiology, 2020)
This study aimed to describe the distribution and characterization of fecal extended-spectrum β-lactamase (ESBL)- and AmpC-producing Escherichia coli isolates from healthy companion animals and cohabiting humans. A total of 968 rectal swab samples from 340 participants, including healthy companion animals and cohabiting humans, were collected from 130 households in South Korea from 2018 to 2019. To determine the bacterial profiles of the participants, several experiments were performed as follows: antimicrobial susceptibility testing, PCR and direct sequencing for ESBL/AmpC production, PFGE, MLST, whole genome sequencing and qRT-PCR. A total of 24.9 and 21.5% of the E. coli isolates from healthy companion animals and cohabiting humans were ESBL/AmpC producers, respectively. The blaCTX–M–14 gene was the most prevalent ESC resistance gene in both pets (n = 25/95, 26.3%) and humans (n = 44/126, 34.9%). The blaCMY–2 gene was also largely detected in pets (n = 19, 20.0%). Overall, intrahousehold pet-human sharing of ESBL/AmpC E. coli isolates occurred in 4.8% of households, and the isolates were all CTX-M-14 producers. In particular, ten CMY-2-producing E. coli isolates from seven dogs and three humans in the different households belonged to the same pulsotype. The MIC values of cefoxitin and the transcription level in CMY-2-producing E. coli isolates were proportional to the blaCMY–2 copy number on the chromosome. Our results showed that the clonal spread of fecal ESBL/AmpC-producing E. coli households’ isolates between healthy companion animals and cohabiting humans was rare, but it could happen. In particular, E. coli ST405 isolates carrying multiple blaCMY–2 genes on the chromosome was sporadically spread between companion animals and humans in South Korea.